Interaction between N6-methyladenosine modification and the tumor microenvironment in colorectal cancer - Jiali Yao; Yeke Song; Xiaoping Yu; Zhijie Lin (Molecular Medicine, 2023)
Abstract The incidence and mortality of colorectal cancer (CRC) are rapidly increasing worldwide. Recently, there has been significant attention given to N6-methyladenosine (m6A), the most common mRNA modification, especially for its effects on CRC development. It is important to note that the progression of CRC would be greatly hindered without the tumor microenvironment (TME). The interaction between CRC cells and their surroundings can activate and influence complex signaling mechanisms of epigenetic changes to affect the survival of tumor cells with a malignant phenotype. Additionally, the TME is influenced by m6A regulatory factors, impacting the progression and prognosis of CRC. In this review, we describe the interactions and specific mechanisms between m6A modification and the metabolic, hypoxia, inflammatory, and immune microenvironments of CRC. Furthermore, we summarize the therapeutic role that m6A modification can play in the CRC microenvironment, and discuss the current status, limitations, and potential future directions in this field. This review aims to provide new insights into the molecular targets and theoretical foundations for the treatment of CRC.